A fuzzy logic based supervisory controller for an FC/UC hybrid vehicular power system - Eren, Y.; Erdinc, O.; Gorgun, H.; Uzunoglu, M.; Vural, B. (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
Depending on growing concerns on energy crises and environmental issues, fuel cell (FC) powered electrical vehicles are favored for possible substitute to conventional internal combustion engine (ICE) based vehicular systems. However, the typical power profile of an automobile motor consisting of transients is not suitable for the use of a sole FC system for vehicle propulsion. This shortcoming could be partly overcome by hybridization. Two potential benefits of combining an FC system with an energy storage unit, ultra-capacitor (UC) has been presented in this study. Firstly, the durability of the FC system could be improved because the additional energy source can fulfill the transient power demand fluctuations. Secondly, the ability of the energy storage source to recover braking energy enhances the fuel economy greatly. An important aspect in designing a hybrid power structure is to find a suitable control strategy that can manage the active power sharing and take advantage of the inherent scalability and robustness benefits of the hybrid system. An integrated procedure for mathematical modeling and power control strategy design for an FC/UC hybrid vehicle is presented in this paper. A fuzzy logic supervisory controller based power management strategy that secures the power balance in hybrid structure, enhances the FC performance and minimizes the power losses is proposed. The main contribution of this paper apart from the previous studies of the authors is the modeling of the complete FC power system with air supply compressor and the integration of the control of the FC system internal dynamics (especially the oxygen excess ratio) into the overall supervisory control structure to maximize the efficiency and durability. To demonstrate the effectiveness of the proposed power management scheme, simulation studies were performed using MATLAB (R), Simulink (R) and SimPowerSystems (R) environments by integrating the detailed mathematical and electrical models of the hybrid vehicular system. Crown Copyright (C) 2009 Published by Elsevier Ltd on behalf of Professor T. Nejat Veziroglu. All rights reserved.
Keywords: Fuel cell; Fuzzy logic; Hybrid electric vehicle; Supervisory control; Ultra-capacitor; ENERGY MANAGEMENT STRATEGY; ELECTRIC VEHICLES; OPTIMIZATION; BATTERIES; Chemistry; Electrochemistry; Energy & Fuels